Assessment of ventilation heterogeneity in severe asthma using phase‐resolved functional lung magnetic resonance imaging - Chuan T. Foo; David Langton; Graham M. Donovan; Bruce R. Thompson; Peter B. Noble; Francis Thien (Physiological Reports, 2025)
Abstract Ventilation heterogeneity is a hallmark of asthma. This study examines the feasibility of phase‐resolved functional lung magnetic resonance imaging (PREFUL MRI) in the evaluation of ventilation heterogeneity in severe asthma, its response to bronchodilator, and correlation with spirometry. Twenty‐three patients with severe asthma and seven healthy volunteers completed PREFUL MRI and spirometry pre and post‐bronchodilator. Ventilation heterogeneity was assessed using ventilation defect percentages (VDP) for regional ventilation (RVent) and flow‐volume loop cross‐correlation (FVL), interquartile distance (IQD), and inhomogeneity index (IHI). Patients exhibited a significantly higher pre‐bronchodilator VDPRVent (19.9 ± 14.0 vs. 1.9 ± 1.9%, p < 0.001), VDPFVL (21.6 ± 15.9 vs. 1.7 ± 2.1%, p < 0.001), IQD (0.60 ± 0.25 vs. 0.30 ± 0.06, p < 0.001), and IHI (0.34 ± 0.12 vs. 0.18 ± 0.04, p < 0.001) compared to healthy volunteers. Post‐bronchodilator, VDPRVent (14.7 ± 12.5 vs. 19.9 ± 14.0%, p = 0.02), IQD (0.51 ± 0.20 vs. 0.60 ± 0.25, p = 0.02), and IHI (0.30 ± 0.11 vs. 0.34 ± 0.12, p = 0.02) decreased significantly in patients but remained significantly higher than in healthy volunteers. Significant correlations were observed between pre‐bronchodilator FEV1 and VDPRVent (ρ = −0.61, p < 0.001), VDPFVL (ρ = −0.73, p < 0.001), IQD (ρ = −0.57, p = <0.001), and IHI (ρ = −0.60, p < 0.001). PREFUL MRI derived markers of ventilation heterogeneity are worse in patients with asthma, improve post‐bronchodilator, and correlate with the severity of airflow obstruction. These findings support the role of PREFUL MRI in assessing ventilation heterogeneity in asthma.